The Waste Isolation Pilot Plant : a potential solution for the disposal of transuranic waste (National Academy Press, 1996)
This volume discusses the readiness of the U.S. Department of Energy's (DOE) Waste Isolation Pilot Plant (WIPP) facility near Carlsbad, New Mexico, to serve as a geological repository for transuranic radioactive waste. WIPP is located in a Permian-age bedded salt deposit 658 meters below the surface. The committee has long reviewed DOE's readiness efforts, now aimed at demonstrating compliance with U.S. Environmental Protection Agency regulations. Site characterization studies and performance assessment modeling are among the topics considered in this volume.